The Cow in the Room - International Livestock Research Institute (International Livestock Research Institute, 2022)
This video is the kick off video for the Cow in the Room Social media campaign and highlights the importance of recognizing the diversity of livestock systems and their social, economic and environmental importance to more than 1.6 billion people worldwide.